Do mergers and acquisitions affect the performance of acquiring firms? Evidence for Swiss small- and medium-sized firms - Spyridon Arvanitis; Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2012)
This paper investigates the post-merger performance effects of mergers and acquisitions (M&As). Our study is based on a representative sample that includes all Swiss M&As that took place in the period 2006-2008. In contrast to previous studies in this field most of our M&As took place between SMEs. Our data allows us to investigate the impact of M&As not only on different measures of economic performance but also on innovation performance. For the empirical analysis we use a matching framework that accounts for endogenous selection. Based on the sample of all M&As we cannot find statistically significant performance effects of M&As for any of the four performance measures. However, we find some positive and statistically significant performance effects when we examine separately specific sub-samples of M&As, namely (a) the M&As with a relative size (as to sales) of the acquired firm of more than 25% of the acquiring firm and (b) the M&As that took place in 2006, i.e. the M&As with the largest time distance between M&A and performance measurement in our sample.
Keywords: L20; O31; 330; mergers and acquisitions; economic performance; innovation performance; Übernahme; Innovation; Unternehmenswachstum; Schweiz